2019
DOI: 10.1111/nmo.13556
|View full text |Cite
|
Sign up to set email alerts
|

Metformin prevents colonic barrier dysfunction by inhibiting mast cell activation in maternal separation‐induced IBS‐like rats

Abstract: Background Intestinal barrier dysfunction is a key etiologic factor of irritable bowel syndrome (IBS). Metformin improves intestinal barrier function, although the underlying mechanism has yet to be fully explained. This study evaluates the protective effect of metformin on colonic barrier integrity and explores the underlying cellular mechanisms. Methods IBS‐like rats were induced by maternal separation. Metformin was administered daily by gavage at 08:30, and rat pups were then separated from their mother. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
(153 reference statements)
0
15
0
Order By: Relevance
“…18 Visceral hypersensitivity could be reduced by blocking MC activation in IBS-like rat models. 35 In this study, we focused on the relationship between MCs and IBS-like symptoms in IBD patients. The present study found that colonic MCs in IBD-IBS patients were significantly more active than those patients without IBS-like symptoms, especially in CD-IBS + patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 Visceral hypersensitivity could be reduced by blocking MC activation in IBS-like rat models. 35 In this study, we focused on the relationship between MCs and IBS-like symptoms in IBD patients. The present study found that colonic MCs in IBD-IBS patients were significantly more active than those patients without IBS-like symptoms, especially in CD-IBS + patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, adult MS rodents show greater immobility time in these tests compared with controls (42,53,58,59,61,62,66,7591) . MS has been associated with decreased sucrose preference (69,71,7577,7981,83,87,9296) and decreased social behaviour with a conspecific (67,72,93,9799) . The effects of MS are not limited to the above alterations of emotional behaviours; numerous studies also report that MS exacerbates motivation for alcohol and drugs of abuse (see (100) for review).…”
Section: The Maternal Separation Modelmentioning
confidence: 99%
“…Interestingly, early-life adversity has been shown to affect enteric nervous system development in a sex-dependent manner, with females being more sensitive than males (255) . MS also produces increased intestinal motility in response to stress, as evidenced by reduced total transit time and increased number of faecal pellets (81,256260) . It has been extensively reported that MS rats display visceral hyperalgesia during colorectal distension (51,67,140,144,146,147,180,220,256,257,259283) .…”
Section: The Maternal Separation Modelmentioning
confidence: 99%
See 2 more Smart Citations